The Regressive Trend of Complex Phenotypic Structures in Neutral Evolution - Dzeverin, I.I. (Вестник зоологии, 2007)
Evolutionary changes of characters formed in ontogeny by developmental induction are modeled for an infinite population and for replicate finite populations under a mutation — drift equilibrium. Induction occurs by interaction of reactants, which must therefore coincide in time intervals of their abilities to react. This mechanism is being damaged in evolution of useless structures by random mutations in genes that control simultaneous formations of reactants, whereas mutational effects on important structures are restrained by selection. The breakdown of induction mechanisms produces increased variability and degeneration in vestigial characters. Quantitative estimations are illustrated by data regarding regressive trends in some groups of mammals. Time spans sufficient for complete loss of vestigial organs obtained from the modelings are much smaller than the periods of macroevolutionary changes. Certain functional value and the genetic correlation with important structures are the most probable mechanisms that could prevent the rapid loss of vestigial structures.